(untitled) (Biological Sciences - PJSIR, 1999)
Hypnea musciformis andBotryocladia leptopoda (red algae),collected fromKarachi coast were studied forchemical investigation andelicitor activity.Ashcontent ofH.musciformis wasbit high(40%).Yieldsof HighMolecular Weight Crude Elicitor Preparations HM.WCEP "Polysaccharides"of two algal genus were high (14-49%) in NaOH extracts. These HMWCEP werechemically analysedfortotal sugarprotein,S04groupanduronicacidcontents. Simpleprofile of monosaccharide consisting of galactose, glucose,fucose, mannose and galactoronic acid weredetected in acid and aqueous extracts ofH. musciformis andB. leptopoda respectivelyascomparedto its alkaline extracts.Elicitor activity of HMWCEP was determined in terms of induced browning in Cicer arietinum (chick pea) tissues. A pronounced browning was produced by the samplestreated with various extracts of H. musciformis. The response was low in the samples treated with various preparations of B. leptopoda.